2018
DOI: 10.1021/acs.est.7b05115
|View full text |Cite
|
Sign up to set email alerts
|

Removal Characteristics of Dissolved Organic Nitrogen and Its Bioavailable Portion in a Postdenitrifying Biofilter: Effect of the C/N Ratio

Abstract: Addition of external carbon sources to postdenitrification biofilters (DNFs) is frequently used in municipal wastewater treatment plants to enhance dissolved inorganic nitrogen removal. However, little is known about its influence on the removal of dissolved organic nitrogen (DON). This study investigated the effect of the carbon-to-nitrogen (C/N) ratio (3, 4, 5, and 6) on the removal characteristics of DON and bioavailable DON (ABDON) in the pilot-scale DNFs treating real secondary effluent. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Given the absence of DON in the synthetic wastewater, all of the effluent DON from AB 1 and AS reactors was mDON. The concentration (1.20 ± 0.36 mg•L −1 , Figure 1b) of mDON derived from AS was consistent with those reported in previous studies, 24,44 indicating the universal limitation of AS-based denitrification processes in minimizing mDON formation. In contrast, AB 1 reactors produced mDON in a significantly (Tukey HSD's p < 0.05) lower concentration (0.21 ± 0.16 mg• L −1 ).…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given the absence of DON in the synthetic wastewater, all of the effluent DON from AB 1 and AS reactors was mDON. The concentration (1.20 ± 0.36 mg•L −1 , Figure 1b) of mDON derived from AS was consistent with those reported in previous studies, 24,44 indicating the universal limitation of AS-based denitrification processes in minimizing mDON formation. In contrast, AB 1 reactors produced mDON in a significantly (Tukey HSD's p < 0.05) lower concentration (0.21 ± 0.16 mg• L −1 ).…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…70 Thus, cyanobacteria-dominated AB may be practically more suitable than chlorophytedominated AB for DON control in wastewater treatment. Particularly for the treatment of low C/N ratio wastewater, which readily causes the overproduction of mDON when using the conventional denitrification process, 24 cyanobacteriadominated AB could have growth advantages over other ABs. 53 Nevertheless, validation based on the direct comparison between the cyanobacteria-and eukaryotic microalgaedominant AB processes is required.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrogen in the wastewater discharged from municipal water resource recovery facility leads to eutrophication of aquatic environments (Hu et al, 2018). Thus, many methods have been considered for improving nitrogen removal.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [6] researched six lakes, including Poyang Lake, and Dongting Lake in Hunan and Jiangxi Provinces, China, and reported that the DON content varied from 17.18 mg/kg to 292.31 mg/kg (mean content, 134.45 mg/kg), comprising 51.86% TDN and 7.14% total nitrogen (TN) across the six lakes; in addition, the distribution of DON was closely related to pollution levels in each lake. The sources of DON are extensive, including sediment, organic matter in the soil, microbial and biological organic debris, and their metabolites [7], besides, the effluent discharged from wastewater treatment plants is also an important source of anthropogenic DON loading to surface waters [8,9], with extremely complex composition [10] that can be bioavailable to aquatic plant species and toxic risk [11].…”
Section: Introductionmentioning
confidence: 99%